Impact of first-trimester anomaly scan on health-related quality of life and healthcare costs: a scoping review - Carsten S. Pietersma; Melek Rousian; Lobke Moolenaar; Eric A. P. Steegers; Annemarie Mulders (Journal of Psychosomatic Obstetrics and Gynecology)
Importance The first-trimester anomaly scan (FTAS) has the potential to detect major congenital anomalies in an early stage of pregnancy. Due to this potential early detection, there is a trend to introduce FTAS in regular care. Data regarding the impact of FTAS on the patient’s perspective are limited.Objective To provide an overview of the literature assessing the impact of the FTAS on health-related quality of life (HRQoL) and healthcare costs.Evidence acquisition Literature search was performed in Embase, PubMed, Medline Ovid, Cochrane Library database, Web-of-Science, and Google Scholar were searched. All studies that reported the performance of a nuchal translucency measurement with a basic fetal assessment HRQoL or healthcare costs of FTAS were included. Studies solely describing screening of chromosomal anomalies were excluded. Three authors independently screened the studies and extracted the data. Results were combined using descriptive analysis. PROSPERO registration number: CRD42016045190.Results The search yielded 3242 articles and 16 were included. Thirteen articles (7045 pregnancies) examined the relationship between FTAS and HRQoL. Anxiety scores were raised temporarily before FTAS and returned to early pregnancy baseline following the absence of anomalies. Depression scores did not change significantly as a result of FTAS. Three articles studied healthcare costs. These studies, published before 2005, found a combination of FTAS and second-trimester anomaly scan (STAS) resulted in an increased amount of detected anomalies when compared to a STAS-only regimen. However, the combination would also be more costly.Conclusions Women experience anxiety in anticipation of the FTAS result and following a reassuring FTAS result, anxiety returns to the baseline level. FTAS seems to be a reassuring experience. The included studies on costs showed the addition of FTAS is likely to increase the number of detected anomalies against an increase in healthcare costs per pregnancy.Review registration: PROSPERO CRD42016045190